ORGANOLEPTIC QUALITY OF BALITBANGTAN SUPERIOR KAMPUNG CHICKEN (KUB) GIVEN WATER EXTRACT OF RED DRAGON FRUIT (Hylocereus polyrhizus) THROUGH DRINKING WATER - N.L.I., Cahyani; Sriyani, N.L.P.; Candrawati, D. P. M. A. (Jurnal Peternakan Tropika; Vol 12 No 4 (2024): Vol. 12 No. 4 Tahun 2024; July - August, 2024)
This study aims to determine the organoleptic quality of KUB chickens given water extract of red dragon fruit peel through drinking water. The analysis used is Non-Parametric Kruskal Wallis and if the results are significantly different then proceed with Mann-Whitney analysis. The treatments consisted of P0 = KUB chickens without extract, P1 = KUB chickens given 3% extract, P2 = KUB chickens given 6% extract, P3 = KUB chickens given 9% extract. The results showed that the color, aroma and tenderness values of the meat were highest in the P3 treatment, which was statistically significantly different (P<0.05) compared to P0, P1 and P2. The highest meat taste value in treatment P3, namely 3.84, was statistically significantly different (P<0.05). The highest overall meat acceptability value in the P3 treatment was 4.28, which was statistically significantly different (P<0.05). The conclusion of this research is that administering 9% water extract of dragon fruit peel through drinking water can improve the organoleptic quality of KUB chicken meat in terms of color, aroma, tenderness and overall acceptability, but does not affect the taste. Providing dragon fruit peel water extract which can improve the organoleptic quality of KUB chicken meat is 9% with an acceptance value of 4.28 (leading to very like it).